PROSES PENERIMAAN, PENGERJAAN, DAN PEMBAYARAN PROYEK PADA SISTEM INFORMASI MANAJEMEN PROYEK DESAIN ARSITEKTUR (STUDI KASUS KONSULTAN ARSITEKTUR XYZ) - Moh. Saiful Hakiki (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2023)
As part of the Architecture, Engineering & Construction (AEC) industry, architectural design projects are carried out by an architectural design studio consulting firm, in which the process of project acceptance, execution and payment is involved. Within the framework of the above process, architectural consulting firm XYZ uses tools in the form of Standard Operating Procedures (SOP) as part of a Management Information System (MIS) in the form of steps, documents and parties where the activity process can be carried out properly and effectively. This is the topic of this paper. The purpose of this paper is that the results can serve as a reference for practitioners and academics in carrying out their work, especially in the field of Management Information Systems for architectural design projects. SOP is prepared using a Flowchart, so that a concise and easy-to-understand flow can be made, for later analysis and evaluation can be carried out based on the sequence of steps of the series of activities carried out. The conclusion obtained is that the process of preparing the SOP on the MIS includes: the project acceptance process involves the Principal Architect and Client/Consumer, the project work process involves the Principal Architect, Design Manager, Architect Staff and Administrative Staff, the project payment process involves the Principal Architect, Design Manager, Staff Administration and Clients, as well as system design, namely with an architectural design project MIS diagram.